Evaluation of strawberry (Fragaria × ananassa Duch.) runner plants production in Tierra del Fuego (54°48'57"S) and transplant yield perfomance in subtropical areas of Argentina - Miserendino, Eduardo (2009)
Presentado al VI International Strawberry Symposium